Effect of strawberry fruit substitution (Fragaria x ananassa) on organoleptic, proximate levels and dietary fiber levels for diabetes mellitus patients - Mia Srimiati; Febry Harsanti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Strawberry is a nutritious food, but the variety of processed foods is still limited; therefore, innovation is required to develop a wider range of strawberry-based products. This study aimed to analyze the effect of strawberry substitution on the characteristics of snack bars. The experimental design employed a completely randomized design (CRD) with three levels of strawberry fruit substitution on the flour: F0 (without strawberries), F1 (25%), F2 (50%), and F3 (75%). All snack bar ingredients were mixed until it became a smooth dough, then baked at 180°C with a low heat setting for 30 minutes. The study was conducted in March-June 2022, with 35 respondents. The organoleptic test data were analyzed with the Kruskal Wallis test and the Mann-Whitney test (data was not normal), the proximate content and dietary fiber were analyzed with a t-test. The result, the organoleptic test revealed that the snack bar with the selected formula was F1 (25%) with proximate results of 5,65% water content, 0,45% ash content, 2,7% protein, 13,93% fat, 27,26% carbohydrates, and food fiber content of 5,68%. Based on the proximate test and dietary fiber content, there was no statistically significant (p= 0,112) difference between the control and F1 formulas. In conclusion, strawberry fruit substitution affects the characteristics of snack bars.